Nuclei near the boundary of neutron stability - Penionzhkevich, Yu (Eurasian Journal of Physics and Functional Materials, 2026)
This article is devoted to the description of the properties of the lightest nuclei with a large excess of neutrons. Light nuclei have always attracted attention due to the wide variety of their properties. While the structural characteristics of medium and heavy nuclei vary fairly smoothly, only single deviations are observed, the structure of light nuclei varies sharply, two neighboring light nuclei are often completely different from each other. This, on the one hand, makes their study a very interesting task, and on the other hand it makes it difficult to identify common trends. Our interest in light neutron-rich nuclei is connected with the desire to observe the characteristic features of nuclei overloaded with neutrons. Recommended Citation Penionzhkevich, Yu. E. (2020) "Nuclei near the boundary of neutron stability," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 3, Article 1. DOI: https://doi.org/10.29317/ejpfm.2020040301